Прогнозування успішності навчання студентів – один із напрямів підвищення якості освіти - Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Kiurchеv, Serhii; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Kuvachov, Volodymyr (My University, 2020)
UK: У статті розглядається один із напрямів підвищення якості навчання студентів шляхом управління рівнем їх знань та умінь за рахунок інформації, отриманої за моделями прогнозування їх успішності з дисциплін залежно від якості проведення навчальних занять. EN: The article one of the ways to improve the quality of student learning by managing their level of knowledge, skills and abilities through the information obtained from the models for predicting their performance in the disciplines depending on the quality of the training sessions are discusses.
Predicting student performance is one of the ways to improve the quality of education
Keywords: якість навчання; успішність; контроль якості освіти; кореляційний аналіз; quality of education; academic performance; education quality control; correlation analysis